Bilateral agreement for the academic year 2007/2009 between Lifelong Learning Programme Universidade Lusíada de Lisboa and Universitat Politècnica de Catalunya - Universidade Lusíada de Lisboa (2016)
- Cooperate in the Socrates/Erasmus activities. - Erasmus subject area: Architecture.